Outage probability analysis of STAR-RIS assisted NOMA network with correlated channels - Wang, T; Badiu, MA; Chen, G; Coon, JP (IEEE, 2022)
In this paper, we investigate the outage probability of a simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) assisted downlink non-orthogonal multiple access (NOMA) network over spatially correlated channels. To evaluate the impact of channel correlations on the system performance, we first approximate the distribution of the composite channel gain as a gamma random variable via a moment-matching approach and then derive new close-form outage probability expressions for a pair of NOMA users. Based on the approximate results, the diversity of each user is studied. Numerical results are provided to validate the effectiveness of the theoretical analysis and illustrate the performance loss due to channel correlations.